Mental and physical health-related quality of life and their associated factors among erectile dysfunction patients in the northeast of Peninsular Malaysia - Ismail, Ahmad Dandarawi (2022)
Introduction: Erectile dysfunction is a common medical problem and affects the quality of life in the patients who suffered this illness. This study aimed to determine the associated factors for quality of life and its association with sexual function among erectile dysfunction patients. It applied a cross-sectional design among erectile dysfunction patients in a men’s health clinic in a tertiary hospital in northeast of Peninsular Malaysia Methodology: The number of participants recruited was 128. Convenient sampling was applied in the selection of eligible participants. The case report form collected responses from medical records and two self-administered questionnaires, namely the 12-Item Short Form Survey and International Index for Erectile Function questionnaire. Descriptive analysis, simple and multiple linear regression confirmatory analyses were performed using SPSS version 26. Conclusion: Age and severity of erectile dysfunction were associated with mental health-related quality of life. Ethnicity and severity of erectile dysfunction were associated with physical health-related quality of life. A healthcare strategy for erectile dysfunction detection and treatment should include early diagnosis of underlying and concomitant disorders, as well as improved patient health and health-related quality of life